Unveiling the Dark Side of Student Finances: A Case Study of Academic Fraud Behavior and Its Impact on Personal Financial Management - Rahayu Wiliana; Anita Mertosono (Pustaka Digital Indonesia, 2026)
Academic integrity and personal financial management are generally examined as separate domains, despite increasing evidence that unethical academic behavior may extend into broader aspects of individual decision-making. This study investigates the behavioral relationship between academic fraud and personal financial management among university students by examining how rationalization mechanisms developed in academic settings influence financial decision-making. A qualitative critical case study design was employed involving twelve undergraduate students from the Faculty of Economics and Business who admitted engaging in academic fraud and simultaneously experienced financial difficulties associated with excessive consumption, Buy Now Pay Later (BNPL), and peer-to-peer lending. Data were collected through semi-structured in-depth interviews and supported by indirect observations of participants’ digital behavior. The findings reveal that rationalization, as conceptualized in Fraud Triangle Theory, represents the strongest behavioral bridge connecting academic dishonesty with irresponsible financial practices. Students who normalized plagiarism, assignment outsourcing, and examination cheating demonstrated similar cognitive justifications when misusing educational funds, accumulating unsustainable digital debt, and prioritizing hedonic consumption over essential educational needs. Self-Regulation Theory further explains that weakened self-control reinforces the transfer of unethical behavior across academic and financial contexts. These findings indicate that academic misconduct is not merely an institutional issue but reflects broader deficiencies in ethical self-regulation affecting financial behavior. The study contributes to the behavioral accounting literature by introducing academic fraud as a precursor to maladaptive personal financial management and recommends integrating ethics education with financial literacy programs to strengthen students’ integrity and long-term financial responsibility.